Trabalho, educação e reprodução social: das sociedades précapitalistas ao capitalismo - Silva, Edivania Maria da (2018)
This study aims at elucidating the function social of the social complex of education, which, created by work, has aided in the reprodution social being the long oh history, shaping according the needs of reprodution each social formation. The research is based on thinking dialectic-marxian, principally in: Karl Marx, in his works O Capital (1996a; 1996b), chapter V Chapter V of Volume I and Chapters XIII and XXIV of Volume II; György Lukács, in Para uma Ontologia do ser social II (2013); István Mészáros, especially in Para além do capital: rumo a uma teoria de transição (2011) and A educação para além do capital (2008); Friedrich Engels, in A situação da classe trabalhadora na Inglaterra (2008); and Mariano Enguita, in A face oculta da escola: educação e trabalho no capitalismo (1989), as well as other authors who study the theme, the exemple: Sérgio Lessa, Trabalho e proletariado no capitalismo contemporâneo (2011) and Capital e Estado de bem-estar: o caráter de classe das políticas públicas (2013); Léo Huberman, História da riqueza do homem (2010); Aníbal Ponce, Educação e luta de classes (1986); Talvanes Maceno, Educação e reprodução social: a perspectiva da crítica marxista (2017); Ivo Tonet, Educação contra o capital (2012); among others. For realization this study was used a research of nature biographic, so like an immanent analysis of the selected texts. As of Marx (1996a) and Lukács (2013), it was learned that work founded the social being, and this being, unlike the inorganic being, in which there is no reproduction, and of the organic being, in which there is always the reproduction of the same, reproduces itself in an uninterrupted way. For that reproduction of the social being to happen, a set of social complexes were created by the work, among them, education. These complexes, unlike work, do not require an exchange of man with nature, but a relation between men themselves. Education emerges concomitantly with work, since every society requires a set of knowledge, behaviors and values that ensures its reproduction. The work, although it has assumed varied forms throughout the modes of production, continues being the base category, the base of sustentation for any society. About education, it also underwent changes, in view that, in each mode of production there are different reproductive needs. In the primitive mode of production, for example, there was an elementary work, the absence of private property, social classes, such that education took place spontaneously and universally. But stem from of slavery, feudalism and capitalism, both work and education were modified according to reproductive needs. Nowadays, in the face of the structural crisis of capital, began in the 1970s, all spheres of social life have been hit. This context, there is the loss of labor rights, chronic unemployment, the destruction of the environment in a way never seen before, as well as an education marked by reforms, which contribute to the maintenance of this mode of production. In front this, the proletariat, while revolutionary subject, must awaken and, through a political revolution with a social soul, to destroy the existing society, as well as all the apparatuses that sustain it, aiming at the construction of a new form sociability, since this crisis not only destroy capital, but also humanity itself.